Like life sculpture, color, and the body - Syson, Luke ca. 20. Jh; Wagstaff, Sheena 1956-; Bowyer, Emerson; Kumar, Brinda (The Metropolitan Museum of Art, 2018)
Since the earliest myths of the sculptor Pygmalion bringing a statue to life through desire, artists have explored the boundaries between sculpture and the physical materiality of the body. This groundbreaking volume examines key sculptural works from 13th-century Europe to the global present, revealing new insights into the strategies artists deploy to blur the distinction between art and life. Sculpture, which has historically taken the human figure as its subject, is presented here in myriad manifestations created by artists ranging from Donatello and Degas to Picasso, Kiki Smith, and Jeff Koons. Featuring works created in traditional media such as wood and marble as well as the unexpected such as wax, metal, and blood, Like Life presents sculpture both conventional and shocking, including effigies, dolls, mannequins, automata, waxworks, and anatomical models. Containing texts by art and cultural historians as well as interviews with contemporary artists, this is a provocative exploration of three-dimensional representations of the human body